Islamic Studies dalam Pendekatan Multidisipliner (Suatu Kajian Gradual Menuju Paradigma Global) - ZA, Tabrani (SCAD Independent, 2014)
Education is a vicious circle phenomenon, which we can not go out with just rely on one approach is diachronic. Moreover, the Islamic education that still has a serious problem faced by most of the drafter of Islamic education is the ability to understand the low level of Islamic education as a â€œscienceâ€ and Islamic education as an â€œeducational institutionâ€. The existence of Islamic education and also should be able to provide a solution to various problems and development needs of the people. Thus, finding new formats in the dynamics of Islamic education is a necessity to help humanity. Here the author tries to describe Islamic education with a combination approach that the synchronic diachronic history of the social sciences, namely sociology and anthropology to bring its characteristics and also the characters. As well as the last author tries to provide an alternative-solution-based approach should be used to study the future of Islamic education.